2020
DOI: 10.1186/s12876-020-01339-3
|View full text |Cite
|
Sign up to set email alerts
|

The risk of rheumatoid arthritis among patients with inflammatory bowel disease: a systematic review and meta-analysis

Abstract: Background: Studies have suggested that patients with inflammatory bowel disease (IBD) have an increased risk of rheumatoid arthritis (RA). However, the available data on this association are inconsistent. This meta-analysis aimed to determine the association between IBD and the risk of RA. Methods: Observational studies investigating the RA risk among patients with IBD (Crohn disease (CD) and/or ulcerative colitis (UC)) were searched in PubMed, Embase, and Web of Science from the date of inception to December… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
0
19
0
2
Order By: Relevance
“…Contrary to our expectations, patients with ulcerative colitis had a greater prevalence of RA in their histories [ 27 , 28 ]. This conflicts with the data presented in the systematic review and meta-analysis, conducted by Chen and coworkers (BMC Gastroenterology 2020 [ 29 ]). As they included eight studies in their meta-analysis, and indeed, most of the studies reported RA to be more prevalent in Crohn’s disease, we believe that perhaps our sample was too small in size to observe this phenomenon.…”
Section: Discussionmentioning
confidence: 57%
“…Contrary to our expectations, patients with ulcerative colitis had a greater prevalence of RA in their histories [ 27 , 28 ]. This conflicts with the data presented in the systematic review and meta-analysis, conducted by Chen and coworkers (BMC Gastroenterology 2020 [ 29 ]). As they included eight studies in their meta-analysis, and indeed, most of the studies reported RA to be more prevalent in Crohn’s disease, we believe that perhaps our sample was too small in size to observe this phenomenon.…”
Section: Discussionmentioning
confidence: 57%
“…For example, perinuclear anti-neutrophil cytoplasmic autoantibodies (p-ANCA) have been found in 26% to 85% of PSC patients and up to 68% of UC patients ( 42 , 43 ). In recent years, an increasing number of studies have noted that rheumatoid arthritis (RA) tended to cluster with IBD ( 44 , 45 ) and that patients with IBD are more likely to develop RA ( 46 ). In addition, anemia is one of the most common extraintestinal systemic complications of IBD, affecting approximately 41-75% of children with IBD ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…This could be the case of patients that have undertaken biologic drugs for other immune mediated inflammatory conditions (IMIDs), whose diagnosis occurred earlier than RA. This possibility is not uncommon since RA patients frequently had history of Crohn's disease, ulcerative colitis or psoriasis 11 , 12 . Moreover, this could also explain the dispensation of the first bDMARD before diagnosis of RA, observed in some patients.…”
Section: Discussionmentioning
confidence: 99%